Experimental and numerical study of the pre-tilted journal bearing. (July 2020) - Mo, Jintao; Luo, Ying; Liu, Jia; Yan, Dapeng; Chen, Xungang; Li, Changxiang; Duan, Chunhui; Zhu, Zihao; Shen, Yueyin; Du, Hua
Hydrodynamic journal bearings are key components for supporting the rotating shafts in high-speed machinery. The shaft misalignment due to the heavy load, the thermal effects, and the manufacturing errors may introduce problems during running such as rub-impact. So the journal bearing with a pre-tilted angle has been introduced in this paper to solve the problem. The pre-tilted journal bearing is allowed to be adjusted to the proper attitude angle according to the tilt of the shaft under working condition. Thus ensuring the symmetric pressure distribution of the bearing and avoiding the rub-impact. A test rig has been designed and built to validate the working effect of the pre-tilted journal bearing. A design method for the pre-tilted journal bearing has also been introduced in this paper. In this method, a transient coupling model is adopted to precisely calculate the attitude angle of the bearing and a special dynamic mesh method is used to guarantee the mesh quality with arbitrary motion of the journal.